Association of quadriceps muscle thickness with the rectus femoris cross-sectional area, muscle strength and gait speed of critically ill patients - Carvalho, Maurício Tatsch Ximenes (2020)
Objective: To verify whether there is an association between quadriceps muscle thickness (QMT) and rectus femoral cross-sectional area (RF), muscle strength and gait speed of critically ill patients. Methods: Cross-sectional study conducted at an adult intensive care unit of a tertiary hospital in southern Brazil. The QMT and RF were measured by ultrasonography, within the first 24 hours of mechanical ventilation, muscle strength was measured using the Medical Research Council scale on the awakening of patient. Gait speed was measured by the 6-m gait speed test at hospital discharge. Results: The sample consisted of 28 patients (46 ± 18 years, 20 males). The QMT showed a strong positive correlation with RF (r=0.708; p <0.0001) and moderate positive correlation with gait speed (r = 0.627; p = 0.003). Multivariate analysis showed the RF was the independent predictor variable of the QMT (β=0.14; p=0.003). Conclusion: The study showed that QMT was associated with rectus femoral cross-sectional area and gait speed of critically ill patients at the evaluated moments. In addition, RF was an independent predictor of EMQ. These results are clinically relevant because they describe the early applicability of quantitative ultrasound measurements in the setting of critically ill patients, as well as the relationship with functional outcomes.